REFORMULATION OF GREEN VICTIMOLOGY ARRANGEMENTS IN THE LAW OF ENVIRONMENTAL PROTECTION AND MANAGEMENT THAT BETTER GUARANTEES LEGAL PROTECTION FOR THE ENVIRONMENT - Ummu Salamah; Prija Djatmika; I Nyoman Nurjaya (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research is motivated by Law Number 32 of 2009 on Environmental Protection and Management, which, in fact, remains limited accommodating the concept of green victimology in the regulation and handling of environmental crimes. Given the prevalence of environmental crimes whose perpetrators are not punished proportionately to the human and non-human losses caused, it is important to question the legal implications of applying the concept of green victimology to the legal protection of environmental victims in the Environmental Protection and Management Law and the regulation of green victimology in the Environmental Protection and Management Law that Better Ensures Legal Protection for the Environment. The type of research used by the author is normative legal research with an explanatory nature. Legal materials for analysis were obtained from primary legal sources in the form of criminal and environmental laws, as well as secondary legal materials from literature on environmental crime and green victimology. The research was conducted through literature review, using a legal and comparative approach, and analyzed qualitatively. The legal implications of applying green victimology in the Environmental Protection and Management Law (UUPPLH) encourage reforms in the definition of victims, the right to sue, recovery mechanisms, as well as sanctions and law enforcement that are more comprehensive and ecological justice. the regulation of Green victimology in the UUPPLH to ensure legal protection for the environment can begin with the reconstruction/reformulation of the UUPPLH by expanding the definition of victims to include the environment as a victim with the right to protection and selected as a subject of environmental law enforcement, up to expanding the definition of victims by including the environment as a victim with the right to protection and selected as a subject of environmental law enforcement.